2020
DOI: 10.1007/s00423-020-01981-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ERAS compliance on the delay between surgery and adjuvant chemotherapy in hepatobiliary and pancreatic malignancies

Abstract: Background Multidisciplinary approach with adjuvant chemotherapy is the key element to provide optimal outcomes in pancreas and liver malignancies. However, post-operative complications may increase the interval between surgery and chemotherapy with negative oncologic effects. Hypothesis and study aim The aim of the study was to analyse whether compliance to Enhanced Recovery After Surgery (ERAS) pathway was associated with decreased interval to adjuvant chemotherapy. Methods Retrospective analysis of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The outcomes and findings of the included studies are displayed in Table 3 . Seventeen studies described oncologic outcomes [ 11 , 12 , 16 23 , 25 , 28 31 , 33 , 35 ], and 20 studies described long-term outcomes [ 10 16 , 22 – 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes and findings of the included studies are displayed in Table 3 . Seventeen studies described oncologic outcomes [ 11 , 12 , 16 23 , 25 , 28 31 , 33 , 35 ], and 20 studies described long-term outcomes [ 10 16 , 22 – 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Half of the studies showed no differences in OS between high and low adherence [ 16 , 22 , 26 ], and half showed improvements in OS by high adherence to ERAS [ 23 , 24 , 34 ]. Two studies reported DFS [ 16 , 25 ]; one showed that high adherence to ERAS could improve 3-year DFS [ 25 ], and the other did not find any difference [ 16 ]. One study showed that high adherence to ERAS could improve 5-year CSS [ 23 ], 2 studies reported that high adherence to ERAS had no effect on 3-year metastasis or 5-year recurrence [ 22 , 23 ], and 1 study showed that high adherence to ERAS reduced the interval from surgery to RIOT [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within these 11 studies[ 6 , 10 , 16 - 24 ], a total of 1852 patients underwent PD and were managed according to their respective institutional clinical pathways. Eight studies[ 6 , 10 , 17 - 19 , 22 - 24 ] stratified patients according to a specific, albeit arbitrary, level of compliance and compared their immediate post-operative outcomes. The characteristics, methodology and conclusions of the included studies are provided in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The 11 studies analyzed (Table 1 ) included 6 prospective[ 10 , 16 , 17 , 21 - 23 ] and 5 retro-spective[ 6 , 18 - 20 , 24 ] studies all published since 2014. There were 2 publications from India[ 11 , 23 ], Canada[ 18 , 20 ] and Italy[ 16 , 22 ], and 1 each from Switzerland[ 19 ], Israel[ 21 ], Sweden[ 24 ] and Greece[ 24 ], all from single centers, with 1 publication from multiple centers in Europe[ 10 ]. The median overall compliance to all components of the clinical pathway was 65.7% (IQR: 62.7%-72.3%) with median compliance to post-operative parameters of the clinical pathway being 44% (IQR: 34.5%-52.25%) in the 4 included studies that reported the values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation